2001
DOI: 10.1017/s0023879100018847
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Archives and Recent Historiography on Colonial Brazil

Abstract: This article draws attention to archival research by Brazilian historians in Portugal and Brazil and the fruits of these labors in monographs, dissertations, and articles. Following a survey of historical writing in the colonial period, this essay discusses the growing movement in the nineteenth and twentieth centuries to preserve documents in libraries, archives, and museums in Brazil. The existence of such institutions spurred divulgation of manuscript collections through journals and published transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Others have shown that colonial and post-colonial fisheries were also capable of overexploiting local organisms, causing a noticeable decline in fish and coral populations (Fogliarini et al, 2022; Sandoval Gallardo et al, 2021). Our understanding of these historical processes has predominantly relied on administrative documents, letters and accounts of European travellers and naturalists who began visiting the region in the 16th century (da Rocha, 2022; Russell-Wood, 2001; Whitehead, 2012). While certain historical sources, such as newspapers and archives, provide valuable descriptions of local plants and animals, along with their broad societal significance (Herbst et al, 2023; Sandoval Gallardo et al, 2021), many written documents produced into the late 18th century lack specific details concerning the relative abundance, distribution, and extent to which several native animals were used (Pádua, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Others have shown that colonial and post-colonial fisheries were also capable of overexploiting local organisms, causing a noticeable decline in fish and coral populations (Fogliarini et al, 2022; Sandoval Gallardo et al, 2021). Our understanding of these historical processes has predominantly relied on administrative documents, letters and accounts of European travellers and naturalists who began visiting the region in the 16th century (da Rocha, 2022; Russell-Wood, 2001; Whitehead, 2012). While certain historical sources, such as newspapers and archives, provide valuable descriptions of local plants and animals, along with their broad societal significance (Herbst et al, 2023; Sandoval Gallardo et al, 2021), many written documents produced into the late 18th century lack specific details concerning the relative abundance, distribution, and extent to which several native animals were used (Pádua, 2000).…”
Section: Introductionmentioning
confidence: 99%